Pelatihan Pembuatan Pestisida Nabati Daun Diwoka (Piper macropiper Pennant.) sebagai Alternatif Pengendalian Hama pada Tanaman Kedelai di Distrik Walesi - Wulandari, Siti Latifa; HardiyantiYM, HardiyantiYM; Takdir, Nuraisyah; Wandik, Busuk; Kogoya, Santi Ferro (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Agricultural development in Walesi District is an area that has a lot of potential for the development of various types of agricultural commodities as a source of income for the Walesi community. Plant Pest Organisms (OPT) both pests and diseases are one of the obstacles in soybean cultivation which can often result in crop failure. The community, especially in the Walesi village area, is actively farming traditionally, especially soybeans, often facing challenges in controlling pests and diseases. Limited knowledge about effective and environmentally friendly control methods. The purpose of the Activity Implementation is to increase Knowledge in controlling soybean plant pests using Diwoka Plant Extract as a Botanical Pesticide. The service method, namely Socialization, is carried out in the form of Lectures, namely about community knowledge regarding plant cultivation techniques, especially soybeans, and the use of natural pesticides from Diwoka plant extract (Piper macropiper Pennant). The training stage is given through direct practice to farmer groups in the Walesi district in making botanical pesticides based on Diwoka leaves (Piper macropiper Pennant). Application of Technology Practice of the process of utilizing natural pesticides on soybean plants and Mentoring and Evaluation. This activity is carried out together and will help the community to understand how to make botanical pesticides. So that later the community can make botanical pesticides independently. Evaluation is the final stage to determine the sustainability of the community service program. The final activity of this community service training is the distribution of questionnaires (post-test) to determine the extent of the development of participants' knowledge, after previously being given a questionnaire (pre-test). Community service activities that focus on training in making botanical pesticides from diwoka leaf extract in Walesi Jayawijaya District have had a significant positive impact. This training has succeeded in increasing farmers' knowledge and skills in managing pests and diseases of soybean plants naturally. Improved skills Farmers have new skills in making and applying botanical pesticides from diwoka leaf extract.